7 years of DDD : tackling complexity in large-scale marketing systems (O'Reilly, 2019)
"It turns out that domain-driven design is not just for cargo shipping. Vladik Khononov (Naxex) explains how he and his team embraced domain-driven design (DDD) (with very limited resources and a very short time to market) at Plexop, a large-scale marketing system that spans over a dozen different business domains. Join in to learn how DDD allowed the team to manage business complexities, find out strategies for defining context boundaries, explore lessons learned the hard way, and discover where they had to adapt the DDD methodology to fit the company's needs. This session was recorded at the 2019 O'Reilly Software Architecture Conference in New York."--Resource description page